2019
DOI: 10.1039/c8tc05401k
|View full text |Cite
|
Sign up to set email alerts
|

How to predict the location of the defect levels induced by 3d transition metal ions at octahedral sites of aluminate phosphors

Abstract: First estimate (left) and accurate estimate (right) of the defect levels of 3d-TM ions at the octahedral sites of aluminate phosphors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Besides, according to Wang et al, oxygen vacancies are easily generated under the anoxic condition, resulting in instability of Mn 4+ . 38,39 However, it has been reported that Ce 4+ can react with oxygen vacancies to form Ce 3+ , 40 so the existence of Ce 4+ in this system can consume oxygen vacancies and stabilize Mn 4+ , which is consistent with the facts described in Figure 2g. Notably, to fully detect the electronic structure of bulk materials, the more advanced technology of X-ray absorption near-edge structure (XANES) spectral measurements is required.…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
“…Besides, according to Wang et al, oxygen vacancies are easily generated under the anoxic condition, resulting in instability of Mn 4+ . 38,39 However, it has been reported that Ce 4+ can react with oxygen vacancies to form Ce 3+ , 40 so the existence of Ce 4+ in this system can consume oxygen vacancies and stabilize Mn 4+ , which is consistent with the facts described in Figure 2g. Notably, to fully detect the electronic structure of bulk materials, the more advanced technology of X-ray absorption near-edge structure (XANES) spectral measurements is required.…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
“…The OTL is defined as shown in the Supporting Information, and the calculated OTL(Cu 2+ ) is about 2.74 eV on the Sr1 site and 2.46 eV on the Sr2 site, roughly in agreement with the experimental result (3.57 eV), considering the calculated OTL always systematically underestimates the experimental chargetransfer energies by about 1 eV. 38 Then, we discuss the long persistent luminescence (LPL) of Sr 1−x Ga 2 O 4 :xCu 2+ phosphors. The undoped SrGa 2 O 4 produces LPL emission, peaking at 406 nm after the sample is exposed to 254 nm UV light for about 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…where I represents the luminescence intensity, and A 0 , A 1 , and A 2 are constants. τ 1 and τ 2 are the luminescence lifetimes, from which the average decay time can be calculated by using the The process of charge transfer from the ligand O 2− ion to Cu 2+ ion could be simulated by the optical transition level (OTL), 38,39 which is the energy needed for an electron at the VBM to transition to the lowest empty 3d state of Cu 2+ . The OTL is defined as shown in the Supporting Information, and the calculated OTL(Cu 2+ ) is about 2.74 eV on the Sr1 site and 2.46 eV on the Sr2 site, roughly in agreement with the experimental result (3.57 eV), considering the calculated OTL always systematically underestimates the experimental chargetransfer energies by about 1 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Exploiting clean and safe sources of energy became a major technological challenge in the 21'st century 1‐3 . Elaborating new materials with high efficiency, low cost, and improved durability will impact on making promising energy technologies 4‐10 . For that reason, new materials such as transition metal‐oxide (TMO) compounds have received much attention from the scientific community.…”
Section: Introductionmentioning
confidence: 99%